Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/mnras/sty429
|View full text |Cite
|
Sign up to set email alerts
|

Stellar photospheric abundances as a probe of discs and planets

Abstract: Protoplanetary disks, debris disks, and disrupted or evaporating planets can all feed accretion onto stars. The photospheric abundances of such stars may then reveal the composition of the accreted material. This is especially likely in B to mid-F type stars, which have radiative envelopes and hence less bulk-photosphere mixing. We present a theoretical framework (CAM) considering diffusion, rotation, and other stellar mixing mechanisms, to describe how the accreted material interacts with the bulk of the star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 92 publications
1
36
0
Order By: Relevance
“…Here we compare our results to the carbon abundance of the HD 163296 star. Its stellar C/H ratio is measured as 1.5 +1.2 −0.7 ×10 −4 (Folsom et al 2012;Jermyn & Kama 2018) which is about half of that in the Sun (2.7 +0.3 −0.3 × 10 −4 , Asplund et al 2009). Therefore HD 163296 system started with relatively carbon poor materials than the ISM.…”
Section: Discussionmentioning
confidence: 98%
“…Here we compare our results to the carbon abundance of the HD 163296 star. Its stellar C/H ratio is measured as 1.5 +1.2 −0.7 ×10 −4 (Folsom et al 2012;Jermyn & Kama 2018) which is about half of that in the Sun (2.7 +0.3 −0.3 × 10 −4 , Asplund et al 2009). Therefore HD 163296 system started with relatively carbon poor materials than the ISM.…”
Section: Discussionmentioning
confidence: 98%
“…Their observable photosphere mass, of order 10 −10 M , can be entirely replaced on a timescale of days at disk accretion ratesṀ acc ∼ 10 −8 to 10 −7 M yr −1 (Jermyn & Kama 2018). Measuring the stellar surface composition is thus a tool for studying the elemental composition of material recently accreted from a circumstellar disk (the Contaminated Astars Method, CAM; Kama et al 2015;Jermyn & Kama 2018). Surface layers built up on the star from dustdepleted material in the protoplanetary disk stage form a small fraction of the total mass of the star, and are lost through diffusive and rotational mixing with the bulk of the star within a million years after the disk dissipates (Jermyn & Kama 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Now let f ph be the mass fraction of accreted material in the photosphere of a star (Jermyn & Kama 2018). Then the observed stellar composition is related to the composition of the accreting material as…”
Section: Refractory Fraction Of An Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since young A stars (Herbig Ae stars) have only a thin convective zone at their surfaces, their surface composition provides a record of their recent accretion history (e.g. Jermyn & Kama 2018). Kama et al (2015) showed that the material Herbig Ae stars accreted from transition discs with large cavities was typically depleted in refractory elements by about a factor of 10 (but not carbon or oxygen), while stars accreting from normal, non-transition discs showed a solar composition.…”
Section: Introductionmentioning
confidence: 99%